Capital, funding liquidity, and bank lending in emerging economies: an application of the LSDVC approach - Dahir, Ahmed Mohamed; Mahat, Fauziah; Ab Razak, Nazrul Hisyam; Amin Noordin, Bany Ariffin (Elsevier, 2019)
The paper examines the effect of funding liquidity on bank loan growth using a dynamic least squares dummy variable corrected (LSDVC) approach over the period between 2006 and 2015. The empirical results reveal that funding liquidity is negative and significant, which suggests that higher funding liquidity reduces bank loan growth. In addition, bank lending improves when bank capital increases and the reduction effect of funding liquidity on bank lending varies with capital. These findings remain robust to an alternative estimator. The study provides implications for policymakers to understand the role of funding liquidity in bank lending.